UJI EFEKTIVITAS KOMBINASI EKSTRAK KULIT KAYU MANIS (Cinnamomum verum J. Presl) DAN DAGING BUAH MAHKOTA DEWA (Phaleria macrocarpa (Scheff.) Boerl.) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL DAN LDL PADA TIKUS PUTIH JANTAN YANG DIINDUKSI ALOKSAN DAN PAKAN - Sunaryo, Hadi; Dwitiyanti, Dwitiyanti; Suriantika, Cipto (Jurnal Farmasi Indonesia, 2018)
Deficiency insulin results increased of lipid in people with diabetes. It happens because of the disruption of insulin function as a result complications of high blood fat levels, especially cholesterol and triglycerides. This research was conduct to determine effec of the combination of Cinnamomum verum extract (KM) and Phaleria macrocarpa extract (MD) on decreasing of total cholesterol and LDL in rat. The research divided into 8 treatment groups that is normal, negative, positive, dose combination 1 (KM 300 mg/kg BB+MD 1000 mg/kg BB), dose combination 2 (KM 300 mg/kg BB+MD 500 mg/kg BB), dose combination 3 (KM 300 mg/kg BB+MD 250 mg/kg BB), dose combination 4 (MD 1000 mg/kg BB+KM 150 mg/kg BB), dose combination 5 (MD 1000 mg/kg BB+KM 75 mg/kg BB). Tukey test results showed a decrease in the optimal combination 4 with a percentage decrease in total cholesterol and LDL by 42.83% and 35.01% but the decline is not comparable to the positive control (atorvastatin) amounted to 47.13% and 47.15%.